Jeszcze raz o konstrukcji i analizie przestrzennych modeli ekonometrycznych produktu krajowego brutto według województw Polski w latach 1999-2003 - Bartosiewicz, Stanisława (One more issue on construction and analysis of spatial econometric models of gross domestic product in Polish voivodships between 1999 and 2003, 2008)
The article discusses, what does Gross Domestic Product per capita in voivodship depend on. The main explanatory variable was the value of investment in current prices per capita and the additional variable was the urbanization index in % of total population in the voivodship. The author of the article suggested the procedure „gradual” construction of linear econometric model.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (20); 2008; nr 1195, s. 9-15